Аркадий Александрович Пластов: [альбом / А. А. Пластов - Пластов Аркадий Александрович (Советский художник, 1978)
Экземпляры: ИСК (20111109) / Инвентарный номер: 696051 / Цена: 5.00 / Сис.шифр: 85.143(2)7-8 / Авт.знак: П 37 / ГРНТИ: 18 / ББК: 85.143(2)7-8